2011
DOI: 10.1007/s00253-011-3170-1
|View full text |Cite
|
Sign up to set email alerts
|

The effect of light, salinity, and nitrogen availability on lipid production by Nannochloropsis sp.

Abstract: We examined responses of batch cultures of the marine microalga Nannochloropsis sp. to combined alterations in salinity (13, 27, and 40 g/l NaCl) and light intensity (170 and 700 μmol photons/m(2)·s). Major growth parameters and lipid productivity (based on total fatty acid determination) were determined in nitrogen-replete and nitrogen-depleted cultures of an initial biomass of 0.8 and 1.4 g/l, respectively. On the nitrogen-replete medium, increases in light intensity and salinity increased the cellular conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
259
3
7

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 488 publications
(286 citation statements)
references
References 39 publications
17
259
3
7
Order By: Relevance
“…However, the neutral lipid class TAG did not change significantly in concentration under the combination of Cd/N stress tested here. This differs from the results of Pal et al (2011), who demonstrated that combinations of stress factors can, under certain circumstances, inhibit neutral lipid synthesis in Nannochloropsis sp., while Gardner et al (2011) showed increased TAG production in C. vulgaris under pH stress and N limitation. This means that the response of C. vulgaris, like any other species, can vary under a combination of stress factors.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…However, the neutral lipid class TAG did not change significantly in concentration under the combination of Cd/N stress tested here. This differs from the results of Pal et al (2011), who demonstrated that combinations of stress factors can, under certain circumstances, inhibit neutral lipid synthesis in Nannochloropsis sp., while Gardner et al (2011) showed increased TAG production in C. vulgaris under pH stress and N limitation. This means that the response of C. vulgaris, like any other species, can vary under a combination of stress factors.…”
Section: Discussioncontrasting
confidence: 55%
“…The inverse relationship we obtained between TAG and PL has been reported previously and suggested to be due to changes in de novo synthesis of both lipid classes, with modification of their metabolic pathways towards the formation and accumulation of neutral lipids; this occurs via the sequestering of de novo-produced fatty acid moieties in the form of TAG in C. vulgaris (Stephenson et al, 2010) and Nannochloropsis sp. (Pal et al, 2011). Accumulation of TAG under these stress conditions may reflect a preferential use of diacylglycerol for triacylglycerol formation rather than use of phosphatidylcholine (PC) and glycosylglycerides for membrane lipid production.…”
Section: Discussionmentioning
confidence: 99%
“…The growth of Dunaliella in the absence of nitrogen might be due to the release of internal nitrogen from the cells. 15 The nitrogen uptake was observed in D. tertiolecta with time (Fig. 1b).…”
Section: Effect Of Nitrogen Concentrationmentioning
confidence: 98%
“…For a cost-effective production of nutrient-rich marine microalgae, with high levels of EPA and/or DHA, it is necessary to select highly productive strains while optimizing cultivation conditions. Besides taxon-specific EPA and DHA variability, intracellular LC-PUFA content may be influenced by growth conditions, such as temperature, irradiance and CO 2 concentration (e.g., Jiang and Gao 2004;Pal et al 2011;Boelen et al 2013). During the course of batch growth or when grown under stress, many microalgal species accumulate lipids, especially TAGs (Hu et al 2008).…”
Section: Introductionmentioning
confidence: 99%